Pemahaman Kosakata Bahasa Inggris untuk Anak-anak melalui Lagu - Ima Widyastuti (Scopus ID 57210281451); Victa Sari Dwi Kurniawati (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2020)
Songs that are combined with movements or dances are still the main media for the delivery of English for children. Unfortunately, children often do not understand the meaning of the lyrics of the songs they sing. This research was conducted to determine the time needed by children to understand the meaning of English vocabulary that is introduced through songs. This study involved 15 Kangaroo PAUD students between the ages of 3-6 years and had been familiar with English for 2-15 months. Within one week, they were able to memorize the 2 songs taught and during 4 days of observation, the understanding of English vocabulary from the lyrics was between 20-90%. The interesting thing is, all participants really understand the meaning of the word thumb, but they have difficulty understanding one word, namely nodding. The discussion of the results of this study is reviewed from the cognitive aspects of acquiring a foreign language by combining two language inputs, namely song and visualization in Total Physical Response.